2006
DOI: 10.1302/0301-620x.88b10.17719
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of subcapital cuneiform osteotomy for the treatment of severe slipped capital femoral epiphysis after skeletal maturity

Abstract: We reviewed prospectively, after skeletal maturity, a series of 24 patients (25 hips) with severe acute-on-chronic slipped capital femoral epiphysis which had been treated by subcapital cuneiform osteotomy. Patients were followed up for a mean of 8 years, 3 months (2 years, 5 months to 16 years, 4 months). Bedrest with 'slings and springs' had been used for a mean of 22 days (19 to 35) in 22 patients, and bedrest alone in two, before definitive surgery. The Iowa hip score, the Harris hip score and Boyer's radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…A number of treatments options were reported for the study population including epiphysiodesis [10,11], pinning in situ (PIS) [1,7,[12][13][14][15][16][17][18][19], closed reduction and pinning (CRIF) [4,5,11,15,16,18,[20][21][22][23][24][25], open reduction and physeal osteotomy (PO) [1,7,15,26] open reduction and internal fixation (ORIF) [23][24][25]27] and surgical dislocation (SD) [13,15,[28][29][30].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…A number of treatments options were reported for the study population including epiphysiodesis [10,11], pinning in situ (PIS) [1,7,[12][13][14][15][16][17][18][19], closed reduction and pinning (CRIF) [4,5,11,15,16,18,[20][21][22][23][24][25], open reduction and physeal osteotomy (PO) [1,7,15,26] open reduction and internal fixation (ORIF) [23][24][25]27] and surgical dislocation (SD) [13,15,[28][29][30].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…4) osteotomies has been limited owing to the high rates of osteonecrosis, but this has been challenged and the outcome may simply be related to surgical experience. 46,47 The Imhäuser intertrochanteric osteotomy 48 has superseded the Southwick subtrochanteric osteotomy 49 and involves resecting a wedge of bone from the intertrochanteric region to correct the flexion, varus and external rotation deformities. The principles of both these osteotomies are similar, producing a reverse deformity distally.…”
Section: Figmentioning
confidence: 99%
“…Such low rates have not been reproduced, but in a series of 25 patients with SCFE treated with Fish's cuneiform osteotomy, the rates of osteonecrosis and OA were respectively 12% and 25% after a mean follow-up of more than eight years. 46 Velasco et al 47 reported the outcome for 66 hips treated with open reduction, 60 of which underwent a subcapital osteotomy as described by Dunn. At a mean followup of 16 years, the rates of osteonecrosis and OA were 11% and 40%, respectively.…”
Section: Figmentioning
confidence: 99%
“…Other authors advise waiting for three weeks, with bed rest to allow the femoral head circulation to recover before surgery for the severe unstable slip. 10 Pinning in situ Stable or unstable slips of mild degree can be pinned in situ, and a good result is usually obtained. A single screw into the central third of the physis on AP & lateral planes is the ideal fixation.…”
Section: Reduction Of Displaced Slips and Timing Of Surgerymentioning
confidence: 99%